(untitled) (Research, Society and Development, 2022)
Objective: To describe remote teaching-learning experiences through the use of active methodologies in undergraduate health courses during the COVID-19 pandemic. Methodology: Integrative review, carried out in April 2021, in the Virtual Health Library (BVS), through the Health Sciences Descriptors (DECS): “Distance Education” and “Methodology”. After applying the search and selection filters through the inclusion and exclusion criteria, a total of 10 studies were selected. Results: A variety of active methodologies are observed in remote teaching with innovative teaching strategies, among them: inverted classroom, discussion of clinical cases, practical activities with family members, synchronous transmission of ward rounds, telecytology, use of social media and telemedicine. The importance of monitoring students is highlighted, as well as effective training of the faculty. Conclusion: Knowledge of these experiences contributes to the execution of online learning, as well as to understanding the difficulties in its use.